(untitled) (GEOMATE Journal, 2024)
In recent years, major earthquakes have caused damage to infrastructure, especially bridge structures. The case of the Gaoliao Bridge collapse following the 6.9 magnitude earthquake in 2022 in Taiwan highlights the importance of conducting performance evaluations during maintenance periods, especially in earthquake-prone areas. Indonesia is located in the Pacific Ring of Fire zone, so earthquakes often occur in several regions of Indonesia, including West Sumatra Province. This study carried out seismic performance evaluations of a prestressed concrete bridge, the STA 6+200 bridge of the Trans Sumatra Toll Road Project, in Padang Pariaman Regency. Seismic performance evaluation of the prestressed concrete bridge was carried out using the finite element method (SAP2000 v21) in terms of the prestressed concrete beam’s bending moment and shear capacity and deflection. In addition, vulnerability analysis using fragility curves was carried out to predict the level of damage to bridge structures due to earthquake loads. A fragility curve through dynamic response analysis of scaled nonlinear time histories (Incremental Dynamic Analysis) due to the Kobe, Imperial Valley, and Northridge earthquakes was developed using a log-normal distribution function. The results of the study show that the moment, shear, and deflection of the prestressed concrete bridge meet the Indonesian bridge permit code. Additionally, the results of the fragility curve show that the prestressed concrete bridge with a PGA value in bridge location of 0.481g has a 26% probability of experiencing slight damage, and there is no possibility of moderate, extensive, and complete damage, indicating that the prestressed concrete bridge structure is effective in ensuring structural safety and resilience.